2000
DOI: 10.1021/ja0017561
|View full text |Cite
|
Sign up to set email alerts
|

How Do Oxidized Thiolate Ligands Affect the Electronic and Reactivity Properties of a Nitrile Hydratase Model Compound?

Abstract: Nitrile hydratases (NHase) are non-heme Fe(III)-containing, or noncorrinoid Co(III)-containing, microbial enzymes that catalyze nitrile hydration. 1 The iron form has been studied most extensively. The Fe(III) active site is low spin (S ) 1 / 2 ), and ligated by three cysteinates, two peptide amide nitrogens and either a hydroxide or an NO. [2][3][4] Given the high amount of sequence homology in the active site region, it is likely that the Co-NHase active site is virtually identical to Fe-NHase. 1,5 In one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
107
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(116 citation statements)
references
References 24 publications
9
107
0
Order By: Relevance
“…[36,37,38] In these cases a tripeptide motif, Cys-Ser-Cys, assumes an N 2 S 2 tetradentate binding array within the protein, and post-translational S-modification renders the cis-dithiolates into a sulfoxide and sulfenate, presumably enhancing the electrophilicity of the Fe or Co metal centers and their ability to bind the substrates, nitrile or thiocyanate. [39] In addition, the sulfoxy units are proposed to orient, via H-bonding, the reactive water molecules so as to efficiently perform the required hydrolyses ( Figure 6). Model studies have found stable S-oxygenates of both Fe and Co analogues as well as those of ruthenium.…”
Section: Nickel Sulfoxygenates As Models Of Oxygendamaged [Nife]h 2 Asementioning
confidence: 99%
“…[36,37,38] In these cases a tripeptide motif, Cys-Ser-Cys, assumes an N 2 S 2 tetradentate binding array within the protein, and post-translational S-modification renders the cis-dithiolates into a sulfoxide and sulfenate, presumably enhancing the electrophilicity of the Fe or Co metal centers and their ability to bind the substrates, nitrile or thiocyanate. [39] In addition, the sulfoxy units are proposed to orient, via H-bonding, the reactive water molecules so as to efficiently perform the required hydrolyses ( Figure 6). Model studies have found stable S-oxygenates of both Fe and Co analogues as well as those of ruthenium.…”
Section: Nickel Sulfoxygenates As Models Of Oxygendamaged [Nife]h 2 Asementioning
confidence: 99%
“…[38][39][40] Only one model has been reported containing both a singly oxygenated and a doubly oxygenated thiolate sulfur in the same molecule. 40 The selective incorporation of an odd number of oxygens is nontrivial, since sulfenates (RS-O(H)) are more reactive than thiolates and readily disproportionate to Herein, the synthesis and characterization of a series of structurally related Fe-NHase model complexes is described, in which the oxidation and protonation states of one of the thiolates are systematically altered. Comparison of the electronic, magnetic, redox, bonding, and reactivity properties of this series reveals how oxo atom addition and protonation affects the metal ion Lewis acidity.…”
mentioning
confidence: 99%
“…37 Very few models containing singly oxygenated sulfurs are available, and none of these contain iron. [38][39][40] Only one model has been reported containing both a singly oxygenated and a doubly oxygenated thiolate sulfur in the same molecule. 40 The selective incorporation of an odd number of oxygens is nontrivial, since sulfenates (RS-O(H)) are more reactive than thiolates and readily disproportionate to sulfinates (RSO 2 − ) and thiolates.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They have also been able to isolate monomeric and dimeric compounds in which the thiolates have been oxidized, although a crystal structure of the monomeric version has not been published. Kovacs' compounds utilize a ligand with an N 3 S 2 donor set consisting of one amino and two imino N atoms and two aliphatic thiolate S atoms [43][44][45]. Structures of both 5-and 6-coordinate (with azide or thiocyanate coligands) have been reported.…”
Section: Comparison To Similar Models and To Active Site Geometrymentioning
confidence: 99%